2022
DOI: 10.3389/fpubh.2022.961726
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 related stressors and mental health outcomes of expatriates in international construction

Abstract: The construction industry is labor-intensive, and employees' mental health has a significant impact on occupational health and job performance. In particular, expatriates in international projects under the normalization of the epidemic are under greater pressure than domestic project employees. This paper aims to explore the association of stressors and mental health in international constructions during COVID-19. Furthermore, test the mediation effect of psychological resilience and moderating effort of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The higher the psychological resilience, the higher the level of mental health, and the more stress-reducing the person is [52,53]. Gao et al [54] found that psychological resilience mediates the relationship between COVID-19-related stressors and psychological well-being in expatriate employees in the international construction industry. Psychological resilience can have an impact on an individual's risky decision-making, and lower psychological resilience may trigger poor decision-making behavior [55].…”
Section: The Mediating Role Of Psychological Resiliencementioning
confidence: 99%
“…The higher the psychological resilience, the higher the level of mental health, and the more stress-reducing the person is [52,53]. Gao et al [54] found that psychological resilience mediates the relationship between COVID-19-related stressors and psychological well-being in expatriate employees in the international construction industry. Psychological resilience can have an impact on an individual's risky decision-making, and lower psychological resilience may trigger poor decision-making behavior [55].…”
Section: The Mediating Role Of Psychological Resiliencementioning
confidence: 99%
“…Researchers have investigated individuals' preventive behaviors against the COVID-19 pandemic (19). At present, many countries have entered the regular prevention and control phase, during which the government's precautions against the pandemic have also become normalized (78). However, little is known about individuals' compliance.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…This may lead to stagnation and loss of overseas programs, particularly in industries where compulsory training requires onsite work, such as the construction industry. 8 Expatriate managers, therefore, expect to determine what kind of people are suitable for expatriation in high-risk situations, meaning that they adapt well to the expatriate environment.…”
Section: Introductionmentioning
confidence: 99%